Recent U.S. Investment Incentives - Towe, Christopher (IMF Working Papers; Working Paper ;, 1993)
The apparent slowdown in U.S. investment and productivity growth in recent years has led to a number of proposals to stimulate investment through the adoption of tax incentives. This paper describes the incentives that were contained in the February 1993 Budget and estimates their effect on the user cost of capital. The recent evidence regarding the effect of tax changes on investment in the United States is reviewed, and the likely effect of the Budget's proposals on investment and overall economic activity is simulated. The simulations suggest that the proposals would have had a stimulative but largely transitory effect on U.S. investment and output.